(untitled) (Majalah Ilmiah UNIKOM, 2023)
The current advancement of information technology has become a crucial factor in various fields, including the healthcare sector. Posyandu is a government program aimed at improving child health in Sindangsari Village. However, there are still shortcomings in its implementation, particularly in the delivery of child health information, monitoring child development, and the lack of child health education for the community. This research aims to develop a website-based information system for Posyandu in Sindangsari Village using the waterfall method to enhance the quality of Posyandu services. The data collection methods used in this study are observation and interviews. The system development method employed is the waterfall method, consisting of requirements analysis, design, programming, testing, and system implementation. The development of the Posyandu information system utilizes PHP programming language, web technologies such as HTML and CSS, and a MySQL database. The system testing is conducted using the Black box method, which aims to ensure the functionality of the system works well and meets the specified requirements. The research findings indicate that the current conditions and processes at Posyandu in Sindangsari Village using the PosyanduQu application have limitations in terms of features and functionality. The developed website-based Posyandu information system is capable of providing more comprehensive and user-friendly features, such as measurement result input, child data management, cadre data management, schedule management, article management, and child development monitoring. Furthermore, this information system also provides a web profile of Posyandu to enhance public interest and participation in Posyandu activities. It is expected that this information system will facilitate cadre management of Posyandu and improve the community’s understanding of the importance of Posyandu in maintaining child health in Sindangsari Village. Key Words: information system, posyandu, waterfall